How entrepreneurs and innovators engage the future and potential business opportunities in South Africa - Brown, Arran Denis (My University, 2018)
This study investigates how entrepreneurs and innovators engage the future, and it reflects on how strategic foresight (also called futures studies) can contribute to innovation and entrepreneurship. The literature emphasises the importance of planning for the future, but not much attention has been given to how entrepreneurs view, forecast and incorporate the future, and how this influences their innovation and creativity. A qualitative approach was used for this study and interviews were carried out with experienced entrepreneurs. The study found that entrepreneurs are disconnected from the future, and do not take it seriously. The future is mostly left to unfold, and it appears as a surprise. Entrepreneurs use simple methods to engage the future, and their understanding of it is vague. There is a lack of leadership and organisation around the future, and very little intervention around the future: everybody seems to be looking around and waiting for something to happen. Nobody seems to know who is responsible or wants to assume responsibility for directing and shaping the future. Entrepreneurs recognise a general connection between the future and innovation, but they fail to see the relationship between innovation and futures studies. Futures studies are central to innovation, especially radical innovation, but entrepreneurs do not exploit it. Incremental innovation is predominant, and this leads us to believe that entrepreneurship is dysfunctional because radical innovation is an important part of entrepreneurship and futures shaping. Entrepreneurs should be trained to use more sophisticated futures studies methods. The link between futures studies and innovation needs to be realised, and there needs to be more leadership around the future. One key recommendation would be to study the extent to which futures studies contribute to innovation and creativity for entrepreneurs: one could teach entrepreneurs futures methods and assess the resultant impact on innovation and creativity.
MBA
Keywords: Entrepreneurship, Innovation, Futures studies, Strategic foresight.